Køn og kærlighed i Den Hebraiske Bibel og tidlig rabbinsk litteratur - Schleicher, Marianne (Rambam. Tidsskrift for jødisk kultur og forskning, 2014)
Gender and Love in the Jewish Bible and Early Rabbinical Literature Based on theories by Michel Foucault, Judith Butler, and Luce Irigaray, the article assumes that every culture must navigate wisely between unequivocal normativity and subversion of norms in the face of the complexity that characterises material culture as a means to secure cultural survival. With analyses of human gender, God’s gender, human love, and God’s love in the Hebrew Bible and early rabbinic literature, the article investigates how portrayals of gender and love regulate Israelite and Rabbinic Jewish culture by disseminating unequivocal norms. It also explains the rationale behind tolerance toward complex, composite, dynamic, and ambiguous variations of gender and love in some of the most dramatic and poetic passages in the founding texts of Israelite and Rabbinic Jewish culture. The article concludes that unequivocal normativity as well as tolerance toward complexity in literary representations of gender and love are subsumed under a discourse that always aims at securing the survival of the cultural by defending reproduction, land, and national identity as the overall objectives.